Latent profiles of body composition indices and their associations with cardiovascular diseases, hypertension, and diabetes: results from the Fasa Adult Cohort study (FACS) - Mehdi Sharafi; Fatemeh Sadat Razavi; Najibullah Baeradeh; Pezhman Bagheri; Afsaneh Rousta; Sima Afrashteh; Maryam Shiravani; Elham Haghjoo (Journal of Health, Population and Nutrition)
Abstract Background The body mass index (BMI) is a common obesity indicator; however, it has limitations in distinguishing between muscle and fat and does not consider fat distribution. This study examines the association between the latent profile of body composition indices and cardiovascular diseases, hypertension, and diabetes. Method This cross-sectional study utilized baseline data from the Fasa Adult Cohort Study (FACS), which included 4,661 participants aged 35 to 70 years. Body composition indices were assessed using bioelectrical impedance analysis (BIA). Latent profile analysis (LPA) was conducted to identify distinct body composition profiles, and the associations between these profiles and the presence of cardiovascular diseases, hypertension, and diabetes were evaluated using multivariable logistic regression models. Results Among diabetes patients, 151 (26.44%) were male. Additionally, 1,218 (93.26%) of smokers were male. There were significant associations between gender and the prevalence of hypertension, diabetes, metabolic syndrome, and cardiovascular disease. The LPA identified five distinct latent profiles, with profiles characterized by higher body fat percentages demonstrating increased odds of diabetes (OR: 5.64, %95CI: 2.86 -to 11.11) and cardiovascular diseases (OR: 2.19, %95CI: 1.11 to 4.31) compared to a low-risk group. Additionally, profiles with higher body fat metrics were associated with significantly increased odds of hypertension (OR: 8.75, 95% CI: 4.60 to 16.65). Conclusion The findings emphasize the complex interplay between body composition and the Odds of NCDs, highlighting the importance of detailed body composition assessments in public health initiatives. Understanding these relationships can inform targeted prevention and management strategies for NCDs.